Pengaruh Hipertensi Terhadap Tajam Penglihatan - sudirman, sudirman (Jurnal Kesehatan Qamarul Huda, 2021)
The aim of this  study was to evaluate the influence of hypertension to visual acuity. This study is non experimental with cross-sectional method and was carried out involving 73 respondents as sample from a population of 244 people aged 40 years, who were taken by simple random sampling in Kopang Primary Health Care, Central Lombok. Statistical analysis shows, this study revealed that the hypertension was significantly (P kurang dari 0.05) influenced to visual acuity was equal to 47.9%, it mean that hypertension was found in 47.9% of those with low vision.